Afforestation-driven increases in terrestrial gross primary productivity are partly offset by urban expansion in Southwest China. (August 2021) - Ding, Zhi; Zheng, Hui; Li, He; Yu, Pujia; Man, Weidong; Liu, Mingyue; Tang, Xuguang; Liu, Ying
Graphical abstract: Highlights: Afforestation (52%) was the dominant LUCC in Southwest China. Legacy effect of afforestation increased more GPP compared with inter-annual effect. The positive effect of afforestation is much better in the karst area. The rapid urban expansion (15.8% y -1 ) might offset more GPP increase in the future. Abstract: Large-scale Ecosystem Restoration Projects (ESPs) have been launched to restore vegetation and increase carbon stocks across China. Whether these ESPs could mitigate the loss of carbon emission due to vegetation degradation caused by human disturbances, such as urban expansion, remains unclear. In this study, we analysed the major human-driven land use and land cover change (LUCC) and evaluated their impacts on gross primary productivity (GPP) dynamics in Southwest China during 2001–2015. Results showed that afforestation, agricultural reclamation, urban expansion and grass planting were the major LUCC. Afforestation accounted for approximately 52% of the LUCC area and greatly contributed to the GPP increase, particularly the multiyear accumulative GPP (5.26 Tg C) in the whole area. Urban expansion only accounted for 20% of the LUCC area and led to the decrease of multiyear accumulative GPP (2.52 Tg C) in the whole area. In terms of legacy effect, afforestation mitigated the GPP decrease caused by urban expansion. However, the urban expansion rate (~15.01% per year) was much faster than that of afforestation (~0.13% per year). Therefore, urban expansion might offset more GPP increase from afforestation in the future. Hence, an effective regulation of urban expansion whilst strengthening conservation efforts is urgently needed to enhance vegetation cover and C stock in Southwest China.